Resource Description Framework Schemas for E-Library - Jamal F. Tawfeq; Saja Majeed Mohammed (Journal of Madenat Alelem University College, 2015)
Libraries can play a major role in the dissemination of knowledge as a huge repository of knowledge. This research shows the description for the content of the electronic library using metadata and Resource Description Framework (RDF) to facilitate access to content at any time based on this description, thus providing a more meaningful search. In this paper provides an integration of computer science techniques with electronic libraries, and determination of semantic features of this content by proposing a new scheme representative in the Resource Description Framework (RDF) and modification of the basic elements in RDF Dublin core.